Pengendalian Biaya Perawatan Peralatan GSE (Ground Support Equipment) Kaitanya dengan Efisiensi Biaya Operasional pada PT Gapura Angkasa Jakarta - Supardji, Supardji; Budiyanto, Enjang Tachyan; Hidayat, Anto (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2010)
Cost control is a very important matter for a company to hold out this day. In a long period of time, profit attainment level influenced by how far a company effective and efficiently managed by, or in other words how far the company definite resources benefit aimed to productive effort. In the company management purpose, in order to carry out cost there must be a control which used by the management to measure and to service the implementation along with compare between result and itâs aim. Itâs cost control in order to make the company to be able to do some operational cost efficiency. The intention of this research is to control maintenance cost in a flight service company. The evaluation done to know whether control maintenance cost was doing good enough to minimized the cost in order to reach efficiency level. The writers do research in PT. Gapura Angkasa located in Soekarno-Hatta Airport branch Cengkareng. In addition PT Gapura Angkasa is a ground handling service company. The research result shows that the control of GSE tools maintenance cost in PT. Gapura Angkasa was basically in a good managed, therefore it reached efficiency level the company expected. But to deal with the uncertainty of world of economy this day such as global financial crisis happened today, thes company should be more careful enough in operational activities. Keywords : Cost Control, Efficiency Cost